Design under uncertainty of solar hot water systems for hospitals - Atienza-Márquez, Antonio; Domínguez Muñoz, Fernando; Fernández Hernández, Francisco; Cejudo López , José Manuel (CLIMA 2022 conference, 2022)
Failed designs are often behind underperforming solar hot water systems and excessive fossil fuel consumption in backup units. This paper proposed a reliable and robust method to design a solar thermal system combined with boilers for hot water preparation in a medium size-hospital hospital building with an average daily demand of 8.69 m3. To start with, the conventional deterministic design, which assumes business-as-usual parameter values and overlooks their uncertainties, gives a required solar caption area of 223.0 m2 to achieve an annual solar fraction of 70%. However, if the uncertainties of input parameters are considered, the reliability of this design solution is barely 22% regarding the solar fraction target set, and a solar caption area of 326 m2 would be required to achieve a reliability of 90%. This work proposes a revised design solution which such high level of trustworthiness but with a lower solar caption area and, therefore, more attractive from an economic perspective. The strategy consists of narrowing the uncertainty bounds of those controllable parameters causing major variance on the system performance. A sensitivity analysis showed that the most significant uncertainties concerning the variance of the solar fraction are the following (in decreasing order of importance): variation of the hot water supplying set-point, insulation defects in the hot water distribution loop, wrong adjustment of thermostatic valves and dust deposition on collectors. According to the improved design proposed rooted in the revision of uncertainties through the installation of high-quality measurement and control equipment and effective maintenance, a design with a solar caption area of 257.3 m2 would be enough to reduce the probability of failure below 10%.